Wage gap between public and private sector analysis in Costa Rica: evidence found based on household surveys from 2006 to 2016 - Ballestero, Andrea (2021)
This document identifies the proportion of the wage gap between the public and private sector in Costa Rica that is due to the difference in the workers’ characteristics, as well as the proportion attributed to the difference in the payment structures, according to 2006 and 2016 household surveys. The results show that the wage gap between the public sector and the private sector in Costa Rica has widened between 2006 and 2016 (approximately from 59% to 64% in the case of men, and from 59% to 66% in the case of women) and that the portion attributable to the difference in the payment structure of each sector has remained remarkably similar for male workers (28% in 2006 and 25% in 2016), while it has increased for female workers (16% in 2006 and 35% in 2016).